Politik Rahim Melalui Ilustrasi Dewi Kilisuci Dalam Naskah Panji Jayakusuma - Khanza' Qutrunnada Azzahro; Munawar Holil (PURBAWIDYA, 2026)
Dewi Kilisuci has long been recognised in Javanese history and literature as a sanctified woman who chose an ascetic life, remaining unmarried and childless. This image has become so firmly entrenched that Kilisuci is commonly understood as a static symbol of purity, detached from political affairs. Previous scholarship has largely reinforced this view, treating Kilisuci as an unchanging emblem of sanctity and consequently limiting analysis to philological readings, ascetic symbolism, and the aesthetic dimensions of her character. However, the manuscript Panji Jayakusuma (PJK) MSS Jav 68 presents a strikingly different narrative. In this text, Kilisuci performs a ritual invocation of the Sun God, Surya, through the Adityahṛdaya mantra in order to obtain a child. This episode directly contradicts her established image as a celibate ascetic and raises a fundamental question, why is the body of a holy woman transformed into a medium of birth? This study seeks to address that question by reading PJK as a textual response to a crisis of sovereignty in Kediri, represented by the figure of an infertile ruler, Ratu Gabuk. By integrating textual analysis with an examination of the manuscript’s illustrations, this research demonstrates that changes in Kilisuci’s body and attire are not merely narrative embellishments but deliberate political strategies. Kilisuci is depicted as undergoing a shift in function, from a secluded ascetic to a spiritual embodiment of the state whose role is to secure dynastic survival. The findings reveal that PJK mobilises the female body as a mechanism for legitimising power. Kilisuci’s pregnancy is not framed as a moral transgression but as a solution to the failure of male authority. In this way, the manuscript suggests that within Javanese literary imagination, sanctity is not a rigid or immutable category but one that can be renegotiated in the interest of preserving the continuity of the state.